Angiotensin II Type 1 Receptor Blockers Reduce Urinary Oxidative Stress Markers in Hypertensive Diabetic Nephropathy - Susumu Ogawa; Takefumi Mori; Kazuhiro Nako; T. KATO; Kazuhisa Takeuchi; Sadayoshi Ito (2006)
We tested the hypothesis that blockade of angiotensin II type 1 receptors reduces oxidative stress markers in parallel with urinary albumin and type IV collagen excretions. Sixty-six diabetic patients with nephropathy were randomly assigned to either the angiotensin II receptor blocker (ARB; n=33) or trichlormethiazide (n=33) group. The majority of patients had been treated with angiotensin-converting enzyme inhibitors or calcium channel blockers for > or =1 year before the present study. Reduction of blood pressure was not different between the 2 groups, and HbA1c levels did not change over the study period (8 weeks). Treatment with ARB (candesartan 8 mg/day, n=11 or valsartan 80 mg/day, n=22) for 8 weeks reduced the levels of plasma monocyte chemoattractant protein 1, interleukin 6, urinary 8-epi-prostaglandin F2alpha, 8-hydroxydeoxyguanosine, albumin, and type IV collagen, whereas the levels of these markers were not altered with trichlormethiazide (2 mg/day). Significant correlation was observed between the reduction of the urinary 8-epi- prostaglandin F2alpha and 8-hydroxydeoxyguanosine and those of the urinary albumin and type IV collagen. Subjects with large oxidative stress had large reduction rates because of ARB administration and showed large urinary albumin suppression. These results suggest that ARBs reduce oxidative stress and inflammation in diabetic patients independent of their effects on blood pressure. In addition, increases in oxidative stress caused by angiotensin II may play an important role in the progression of diabetic nephropathy. Our results may help to explain the clinical observation that ARB reduces urinary albumin excretion very efficiently in some patients but not in others.